Effect of Quality of Caregiver–Adolescent Relationship on Sexual Debut, Transactional Sex, and on Age-Disparate Relationships Among Young Women in Rural South Africa Enrolled in HPTN 068. (1st April 2022) - Shangase, Nosipho; Edwards, Jess; Pence, Brian; Aiello, Allison; Hussong, Andrea; Gómez-Olivé, Xavier; Kahn, Kathleen; Stoner, Marie; Pettifor, Audrey
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Adolescent girls and young women (AGYW) remain burdened by the HIV epidemic. Positive caregiver–child relationships are associated with safe sexual behaviors in young people; yet, this literature often highlights the role of parent–child communication and parental monitoring, neglecting the importance of emotional relationships between a caregiver and adolescent. Setting: We used longitudinal data from HIV Prevention Trial Network 068—conducted among 2533 AGYW (13–20 years) over a period of 5 years in Agincourt, South Africa. Method: Kaplan–Meier and Cox models were used to estimate the effect of quality of caregiver–adolescent relationships (caring and closeness) on sexual debut, and log-binomial models with generalized estimating equations were used to examine the relationship between our exposures and transactional sex and age-disparate relationships. Results: Sexual debut was delayed among those who reported high levels of caregiver caring [hazard ratio: 0.80, 95% confidence interval (CI): 0.69 to 0.93] and caregiver closeness (hazard ratio: 0.80, 95% CI: 0.68 to 0.95). AGYW who reported high quality caregiver–adolescent relationships had a lower risk of transactional sex [caring: risk ratio (RR): 0.67, 95% CI: 0.58 to 0.78; closeness: RR: 0.58; 95% CI: 0.50 to 0.67]. Similarly, those with high-quality caregiver–adolescent relationships were less likely to be in an age-disparate relationship (caring: RR: 0.68, 95% CI: 0.58 to 0.79; closeness: RR: 0.77, 95% CI: 0.66 to 0.90). Conclusions: Findings indicate high-quality caregiver–adolescent relationships are associated with delayed sexual debut, a lower risk of transactional sex, and having an older partner. Family-centered interventions are needed to improve relationships between AGYW and caregivers.